Intelligent computing systems : second International Symposium, ISICS 2018, Mérida, Mexico, March 21-23, 2018, Proceedings /: second International Symposium, ISICS 2018, Mérida, Mexico, March 21-23, 2018, Proceedings. ([2018]) - Unknown
No abstract available